Application of a nucleophilic substitution reaction for spectrofluorimetric quantification of ketamine in pharmaceutical and plasma matrices - Reem M. Alnemari; Maram H. Abduljabbar; Yusuf S. Althobaiti; Farooq M. Almutairi; Muneef M. Aldhafeeri; Atiah H. Almalki; Sherif Ramzy (Scientific Reports)
Abstract Ketamine is a dissociative anesthetic drug that is abused by teenagers and young adults, commonly for recreational purposes in dance clubs, to generate euphoria and dissociation, and sometimes employed as a date-rape drug. Herein, a highly sensitive, and environmentally friendly spectrofluorimetric method was developed for detection of ketamine in pharmaceutical and plasma samples. The technique is based on a nucleophilic substitution reaction occurring between ketamine and NBD-Cl (4-chloro-7-nitrobenzo-2-oxa-1,3-diazole), resulting in the formation of a fluorescent derivative that exhibits detectability at a remarkable level. The resultant derivative demonstrates its maximum emission intensity at 543 nm upon excitation at a wavelength of 481 nm. Upon optimizing the reaction parameters, a linear relationship was established between the fluorescence intensity of the formed derivative and the concentrations of ketamine within the specified range of 10 − 250 ng/mL. The method demonstrated exceptional sensitivity with detection and quantitation limits of 2.37 ng/mL and 7.18 ng/mL, respectively, allowing for the detection of ketamine in both pharmaceutical and plasma samples. The method was precise (%RSD < 1) accurate (%R = 99.74%) and robust (% R ± SD from 98.00 ± 1.11 to 99.97 ± 0.75). Furthermore, the developed method was compared to the reported method, with the results indicating that the suggested method is more sensitive and ecologically benign.